Anterior Nucleus of the Thalamus Deep Brain Stimulation with Concomitant Vagus Nerve Stimulation for Drug-Resistant Epilepsy. Issue 4 (31st July 2021) - Parisi, Veronica; Lundstrom, Brian Nils; Kerezoudis, Panagiotis; Alcala Zermeno, Juan Luis; Worrell, Gregory A; Van Gompel, Jamie J
Abstract: BACKGROUND: The Food and Drug Administration approved the deep brain stimulation of the anterior nucleus of the thalamus (ANT-DBS) as an adjunctive therapy for drug-resistant epilepsy (DRE) in the United States in 2018. The DBS Therapy for Epilepsy Post-Approval Study is further evaluating the safety and effectiveness of ANT-DBS among different patients' groups. For this study, devices for vagus nerve stimulation (VNS) must be removed prior to enrolment. OBJECTIVE: To investigate the outcomes of concomitant ANT-DBS and VNS treatment for DRE. METHODS: A retrospective analysis was performed for 33 patients who underwent ANT-DBS using previous VNS to define distinct subgroups: standard ANT-DBS (9 subjects), ANT-DBS with functional VNS (12 subjects), and ANT-DBS with the VNS implantable pulse generator explanted or turned off at the time of the DBS (12 subjects). Effectiveness and safety data were analyzed across the whole population and among subgroups. RESULTS: A mean decrease in seizure frequency of 55% was observed after a mean follow-up of 25.5 mo. Approximately 67% of patients experienced ≥50% reduction in seizure frequency. Seizure reduction percentage was not significantly different among groups. Approximately 50% of subjects with no appreciable improvement and 75% of those who showed benefit after VNS (including improvement in seizure frequency, seizure severity, and seizure duration or quality of life) achieved a seizure reduction ≥50% after ANT-DBS surgery. There were no complications related to concomitant VNS and ANT-DBS. CONCLUSION: ANT-DBS for DRE provides excellent results despite previous and ongoing VNS therapy. Removal of VNS does not appear to be necessary before ANT-DBS. Graphical Abstract: